Web building behavior in a wall spider (Oecobiidae) suggests a close relationship with orb-weavers. Issue 1 (2nd January 2023) - Solano-Brenes, Diego; Muniz, Danilo G.; Sandoval, Luis; Alvarado-Rodríguez, Olman; Barrantes, Gilbert
Abstract : Behavior is often phylogenetically informative and detailed descriptions of behavior have been used to support taxonomic relationships in several groups, such as birds, lizards, and arthropods. Web building behavior has provided informative traits to several spider families, but observations are lacking for other families, such as wall spiders Oecobiidae. Recent phylogenetic hypotheses based on molecular traits placed oecobiids either close to cribellate orb weavers (Uloboridae) or to long-spinneret spiders (Hersiliidae). Here, we describe for first time the web construction behavior and details of the web design in the oecobiid Oecobius concinnus Simon 1893 (Oecobiidae). We compare them with uloborid and araneoid orb weavers. If Oecobiidae and Uloboridae are closely related, we expect that O. concinnus share some web construction behaviors with these orb weavers. Video recordings and analyses of web structures suggest the sequence of web construction (radii, then sticky spiral construction) and the arrangement of cribellate threads are possible homologies between Oecobiidae and orb weavers, supporting a close relationship of Oecobiidae with Uloboridae.